Coupling between arterial pressure, cerebral blood velocity, and cerebral tissue oxygenation with spontaneous and forced oscillations - Rickards, Caroline A (Physiol Meas, 2015)
We tested the hypothesis that transmission of arterial pressure to brain tissue oxygenation is low under conditions of arterial pressure instability. Two experimental models of hemodynamic instability were used in healthy human volunteers; (1) oscillatory lower body negative pressure (OLBNP) (N = 8; 5 male, 3 female), and; (2) maximal LBNP to presyncope (N = 21; 13 male, 8 female). Mean arterial pressure (MAP), middle cerebral artery velocity (MCAv), and cerebral tissue oxygen saturation (ScO(2)) were measured non-invasively. For the OLBNP protocol, between 0 and −60mmHg negative pressure was applied for 20 cycles at 0.05 Hz, then 20 cycles at 0.1 Hz. For the maximal LBNP protocol, progressive 5 min stages of chamber decompression were applied until the onset of presyncope. Spectral power of MAP, mean MCAv, and scO(2) were calculated within the VLF (0.04–0.07 Hz), and LF (0.07–0.2Hz) ranges, and cross-spectral coherence was calculated for MAP-mean MCAv, MAP-ScO(2), and mean MCAv-ScO(2) at baseline, during each OLBNP protocol, and at the level prior to pre-syncope during maximal LBNP (sub-max). The key findings are (1) both 0.11-IZ OLBNP and sub-max LBNP elicited increases in LF power for MAP, mean MCAv, and scO(2) (p ≤ 0.08); (2) 0.05 Hz OLBNP increased VLF power in MAP and scO(2) only (p ≤ 0.06); (3) coherence between MAP-mean MCAv was consistently higher (≥0.71) compared with MAP-ScO(2), and mean MCAv-ScO(2) (≤0.43) during both OLBNP protocols, and sub-max LBNP (p ≤ 0.04). These data indicate high linearity between pressure and cerebral blood flow variations, but reduced linearity between cerebral tissue oxygenation and both arterial pressure and cerebral blood flow. Measuring arterial pressure variability may not always provide adequate information about the downstream effects on cerebral tissue oxygenation, the key end-point of interest for neuronal viability.